Systematic single-cell analysis provides new insights into heterogeneity and plasticity of the pancreas - Tritschler, Sophie; Theis, Fabian J.; Licked, Heiko; Boettcher, Anika (Molecular Metabolism, 2017)
Background Diabetes mellitus is characterized by loss or dysfunction of insulin-producing β-cells in the pancreas, resulting in failure of blood glucose regulation and devastating secondary complications. Thus, β-cells are currently the prime target for cell-replacement and regenerative therapy. Triggering endogenous repair is a promising strategy to restore β-cell mass and normoglycemia in diabetic patients. Potential strategies include targeting specific β-cell subpopulations to increase proliferation or maturation. Alternatively, transdifferentiation of pancreatic islet cells (e.g. α- or δ-cells), extra-islet cells (acinar and ductal cells), hepatocytes, or intestinal cells into insulin-producing cells might improve glycemic control. To this end, it is crucial to systematically characterize and unravel the transcriptional program of all pancreatic cell types at the molecular level in homeostasis and disease. Furthermore, it is necessary to better determine the underlying mechanisms of β-cell maturation, maintenance, and dysfunction in diabetes, to identify and molecularly profile endocrine subpopulations with regenerative potential, and to translate the findings from mice to man. Recent approaches in single-cell biology started to illuminate heterogeneity and plasticity in the pancreas that might be targeted for β-cell regeneration in diabetic patients. Scope of review This review discusses recent literature on single-cell analysis including single-cell RNA sequencing, single-cell mass cytometry, and flow cytometry of pancreatic cell types in the context of mechanisms of endogenous β-cell regeneration. We discuss new findings on the regulation of postnatal β-cell proliferation and maturation. We highlight how single-cell analysis recapitulates described principles of functional β-cell heterogeneity in animal models and adds new knowledge on the extent of β-cell heterogeneity in humans as well as its role in homeostasis and disease. Furthermore, we summarize the findings on cell subpopulations with regenerative potential that might enable the formation of new β-cells in diseased state. Finally, we review new data on the transcriptional program and function of rare pancreatic cell types and their implication in diabetes. Major conclusion Novel, single-cell technologies offer high molecular resolution of cellular heterogeneity within the pancreas and provide information on processes and factors that govern β-cell homeostasis, proliferation, and maturation. Eventually, these technologies might lead to the characterization of cells with regenerative potential and unravel disease-associated changes in gene expression to identify cellular and molecular targets for therapy.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Dedifferentiation; Diabetes; Endocrine cells; Maturation; Regeneration; Single-cell analysis; Subpopulations; Transdifferentiation; β-Cell heterogeneity